Begonia yizhouensis, a new species in Begonia sect. Coelocentrum (Begoniaceae) from Guangxi, China - Tong, Yi; Tian, Dai-Ke; Shu, Jiang-Ping; Xiao, Yan; Wang, Bing-Mou; Fu, Nai-Feng (Phytotaxa, 2019)
Begonia yizhouensis, a new species in Begonia sect. Coelocentrum (Begoniaceae) from Guangxi of China, is described and illustrated. Morphologically, it is similar to the adjacently distributed B. luochengensis, but clearly separated by its waxy leaves with glabrous or sometimes sparsely puberulous surfaces, larger variation in leaf color and maculation along the main veins, white to pinkish-white flowers and late flowering. Furthermore, molecular phylogenetic analysis indicated B. yizhouensis was a monophyletic lineage and was sister with B. luochengensis. The relationship of the new species and other similar species is also discussed. This new species is endemic to limestone hills in Guangxi and is assessed as “Endangered” (EN) according to the IUCN Red List Categories and Criteria. Additionally, morphological and molecular evidence for B. yishanensis not being synonymous with B. porteri is presented.